2020
DOI: 10.1136/bmjgh-2019-002227
|View full text |Cite
|
Sign up to set email alerts
|

Cuba y seguridad sanitaria mundial: Cuba’s role in global health security

Abstract: Cuba has been largely absent in academic and policy discourse on global health security, yet Cuba’s history of medical internationalism and its domestic health system have much to offer contemporary global health security debates. In this paper, we examine what we identify as key traits of Cuban health security, as they play out on both international and domestic fronts. We argue that Cuba demonstrates a strong health security capacity, both in terms of its health systems support and crisis response activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
5
0
6
Order By: Relevance
“…Driven underground, these services become unsafe. During the 2016 Zika outbreak -a virus that affects fetal development, manifesting in babies with abnormally small heads, or microcephaly -no national policy changed to increase access to reproductive-health services 14 . As a consequence, women in the Zika epicentre -in Brazil, Colombia and El Salvador -told us, in work currently under peer review, that they sought unsafe abortions through providers they found online, feminist groups and the black market.…”
Section: Sexual and Reproductive Healthmentioning
confidence: 99%
“…Driven underground, these services become unsafe. During the 2016 Zika outbreak -a virus that affects fetal development, manifesting in babies with abnormally small heads, or microcephaly -no national policy changed to increase access to reproductive-health services 14 . As a consequence, women in the Zika epicentre -in Brazil, Colombia and El Salvador -told us, in work currently under peer review, that they sought unsafe abortions through providers they found online, feminist groups and the black market.…”
Section: Sexual and Reproductive Healthmentioning
confidence: 99%
“…Among the top 20 countries in the HPI, Cuba is the only non-high-income group country with an HPI ranking of 11th, and it had the lowest HRPI throughout the study period. Previous studies have found Cuba to be among the highest ranked countries globally in all health indicators [142,143]. This is largely due to its universal healthcare system, with the achievable primary healthcare focusing on prevention, priorities the right to health of the poor and vulnerable [144,145].…”
Section: Discussionmentioning
confidence: 99%
“…Yet it has managed to achieve levels of life expectancy and infant mortality that (even after adjusting for possible data manipulation) [1][2][3] surpass those observed in advanced economies. [4][5][6][7][8] Cuba is not the sole non-democratic regime to have achieved similar outcomes. The former Union of Soviet Socialist Republics (USSR) also stands as a clear example of such a case where there was a rapid increase in health outcomes post-1945, which made the USSR compare favourably with Western Europe [9][10][11] in spite of the fact that it was relatively poorer.…”
Section: Introductionmentioning
confidence: 98%
“…46 In addition, there is also the role of underground clinics, where some patients expend private resources to obtain care. Sources: See ref 8 ; Pan American Health Organization 56 World Health Organization 57 . *The WHO data repository did not provide observations for all countries in Latin America.…”
Section: Introductionmentioning
confidence: 99%